Glycoengineering of E‐Selectin Ligands by Intracellular versus Extracellular Fucosylation Differentially Affects Osteotropism of Human Mesenchymal Stem Cells. (17th July 2016) - Dykstra, Brad; Lee, Jungmin; Mortensen, Luke J.; Yu, Haixiao; Wu, Zhengliang L.; Lin, Charles P.; Rossi, Derrick J.; Sackstein, Robert
Abstract: Human mesenchymal stem cells (MSCs) hold great promise in cellular therapeutics for skeletal diseases but lack expression of E‐selectin ligands that direct homing of blood‐borne cells to bone marrow. Previously, we described a method to engineer E‐selectin ligands on the MSC surface by exofucosylating cells with fucosyltransferase VI (FTVI) and its donor sugar, GDP‐Fucose, enforcing transient surface expression of the potent E‐selectin ligand HCELL with resultant enhanced osteotropism of intravenously administered cells. Here, we sought to determine whether E‐selectin ligands created via FTVI‐exofucosylation are distinct in identity and function to those created by FTVI expressed intracellularly. To this end, we introduced synthetic modified mRNA encoding FTVI ( FUT6‐ modRNA) into human MSCs. FTVI‐exofucosylation (i.e., extracellular fucosylation) and FUT6‐ modRNA transfection (i.e., intracellular fucosylation) produced similar peak increases in cell surface E‐selectin ligand levels, and shear‐based functional assays showed comparable increases in tethering/rolling on human endothelial cells expressing E‐selectin. However, biochemical analyses revealed that intracellular fucosylation induced expression of both intracellular and cell surface E‐selectin ligands and also induced a more sustained expression of E‐selectin ligands compared to extracellular fucosylation. Notably, live imaging studies to assess homing of human MSC to mouse calvarium revealed more osteotropism following intravenous administration of intracellularly‐fucosylated cells compared to extracellularly‐fucosylated cells. This study represents the first direct analysis of E‐selectin ligand expression programmed on human MSCs by FTVI‐mediated intracellular versus extracellular fucosylation. The observed differential biologic effects of FTVI activity in these two contexts may yield new strategies for improving the efficacy of human MSCs in clinical applications. Stem Cells 2016;34:2501–2511 Abstract : Two complimentary approaches were used to create E‐selectin ligands on human mesenchymal stem cells (MSC) using fucosyltransferase VI (FTVI): extracellularly, by treating cells with purified FTVI enzyme, and intracellularly, by transfecting cells with FTVI‐encoding modified mRNA. The extent to which the newly created E‐selectin ligands could improve MSC homing to bone was tested using in vivo calvarial imaging. This three‐dimensional reconstruction of a xenotransplanted mouse calvarium region shows bone (grey) and blood vessels (red), 24 hours after intravenously co‐transplanting fucosylated MSCs (blue) and control MSCs (green). Both fucosylation approaches significantly increased homing of MSCs to the bone marrow, but intracellularly fucosylated ( FUT 6‐mod) MSCs demonstrated increased extravasation into bone marrow parenchyma compared to their exofucosylated counterparts (FTVI‐exo). The observed differential biologic effects of FTVI activity in these two contexts may yield new strategies for improving the efficacy of human MSCs in clinical applications. **p < 0.01